Aphasia Screening Test (TeRAp): Construction and Validation for European Portuguese - Fonseca, José (2024)
Introduction: Aphasia is a common acquired language disorder following stroke or other brain injuries. However, it is not always easy to make a differential diagnosis with another communication disorder. Communication assessment in acute phases of the stroke, when the patient is bedridden or when there is no time for a more in-depth assessment, needs to be done with a formal screening test that has normative data. The aim of this study was to develop the Aphasia Screening Test (TeRAp) in digital format (appWeb) and present its clinimetric values.Methods: A screening test (TeRAp) was built in appWeb format that assesses the main areas of language processing and automatically provides a diagnostic hypothesis. A group of people with aphasia was evaluated and their performance was compared with three control groups, one of healthy people and two groups of people with neurological conditions, one with dysarthria and the other with mild cognitive impairment.Results: Ceiling values were obtained in all the tests. Sensitivity values of 1 and specificity values of 0.99 were obtained for the presence of aphasia. Conclusion: An online aphasia screening test was developed, with excellent sensitivity and specificity results, which can be used by any health professional.